Addressing the “black box” of focused deterrence: an examination of the mechanisms of change in Chicago’s Project Safe Neighborhoods - Trinkner, Rick (Journal of experimental criminology, 2019)
Chicago’s Project Safe Neighborhoods focused deterrence program is an effective crime reduction policy. However, similar to other focused deterrence programs, prior evaluations have not empirically established the mechanisms of change believed to underlie the program. The purpose of this paper was to address this gap by examining the influence of offender notification meetings—a key component of the program—on three mechanisms: perceptions of risks associated with future offending, perceptions of police legitimacy, and adherence to community norms.